Transient Small Bowel Angio-oedema Secondary to Intravenous Iodinated Contrast Medium - Kalam, Amjada A.; Ramaswamy, Praveen Kesav (Journal of Gastrointestinal and Abdominal Radiology, 2022)
We report the clinical profile and computed tomography (CT) findings of a rare case of transient angio-edema of the small bowel following intravenous administration of non-ionic iodinated contrast material in a 36-year-old woman. The pre-contrast CT showed normal small bowel and large bowel wall thickness. Findings included long segment, circumferential bowel wall thickening involving the duodenum, jejunum, and almost the entire ileum on CT scan obtained following the intravenous contrast material injection. The large bowel wall appeared normal in post contrast images also. There was no mesenteric fat stranding, ascites or significant lymphadenopathy. This entity, like most contrast-induced adverse reactions, has a favorable clinical outcome with aggressive clinical monitoring and supportive measures.
Keywords: anaphylaxis; contrast allergy; small bowel angio-edema